2022
DOI: 10.26508/lsa.202201458
|View full text |Cite
|
Sign up to set email alerts
|

ScRNA-seq expression ofIFI27andAPOC2identifies four alveolar macrophage superclusters in healthy BALF

Abstract: Alveolar macrophages (AMs) reside on the luminal surface of the airways and alveoli, ensuring proper gas exchange by ingesting cellular debris and pathogens, and regulating inflammatory responses. Therefore, understanding the heterogeneity and diverse roles played by AMs, interstitial macrophages, and recruited monocytes is critical for treating airway diseases. We performed single-cell RNA sequencing on 113,213 bronchoalveolar lavage cells from four healthy and three uninflamed cystic fibrosis subjects and id… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 80 publications
(119 reference statements)
1
19
0
Order By: Relevance
“…IFI27 is also upregulated in the peripheral blood of COVID-19 patients ( 10 , 11 , 13 ) and may serve as a biomarker for pre-symptomatic SARS-CoV-2 infection ( 14 ). These data are consistent with observations that the induction of type I interferons in the lower respiratory tract and systemically is associated with immunopathology ( 15 ) whilst the induction of type I interferons in the upper respiratory tract is associated with virus control and not disease outcomes ( 12 ). However, others have suggested that IFI27 expression is low in patients with severe COVID ( 16 , 17 ).…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…IFI27 is also upregulated in the peripheral blood of COVID-19 patients ( 10 , 11 , 13 ) and may serve as a biomarker for pre-symptomatic SARS-CoV-2 infection ( 14 ). These data are consistent with observations that the induction of type I interferons in the lower respiratory tract and systemically is associated with immunopathology ( 15 ) whilst the induction of type I interferons in the upper respiratory tract is associated with virus control and not disease outcomes ( 12 ). However, others have suggested that IFI27 expression is low in patients with severe COVID ( 16 , 17 ).…”
Section: Introductionsupporting
confidence: 91%
“…Preliminary evidence suggests that IFI27 expression may be a useful biomarker for COVID-19 diagnosis ( 8 11 ). In the respiratory tract, IFI27 expression is significantly upregulated by SARS-CoV-2 infection, more so than by other respiratory viruses ( 8 , 9 , 12 ). IFI27 is also upregulated in the peripheral blood of COVID-19 patients ( 10 , 11 , 13 ) and may serve as a biomarker for pre-symptomatic SARS-CoV-2 infection ( 14 ).…”
Section: Introductionmentioning
confidence: 97%
“…Inhibiting the classical NF-κB signaling pathway blocks growth hormone (GH) or insulin-like growth factor (IGF-1) signaling, suppresses cell proliferation, and suppresses bone morphogenetic protein 2 (BMP2) expression, thereby promoting apoptosis (Jimi et al, 2019). Most importantly, these three genes were all involved a lot in the inflammatory response (Zhang Z. et al, 2021;Zhu et al, 2021;Li et al, 2022), stating that inflammatory response was a main regulated pathway in IPF and these three genes could modulate the pathological process of IPF through this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Dataset (GSE193782) was derived from the Gene Expression Omnibus database (GEO) ( https://www.ncbi.nlm.nih.gov/geo/ ). Single-cell sequencing data from four healthy controls and three CF patients were included in the GSE193782 dataset ( 18 ). Bronchoalveolar lavage fluid (BALF) was used as the sample in the study.…”
Section: Methodsmentioning
confidence: 99%